2010
DOI: 10.1021/es100273b
|View full text |Cite
|
Sign up to set email alerts
|

New Method and Detection of High Concentrations of Monomethylarsonous Acid Detected in Contaminated Groundwater

Abstract: Monomethylarsonous acid (MMAIII) was detected in groundwater from a former herbicide production plant in the USA. The site has total arsenic concentrations up to thousands of mg/L, representing one of the most severe cases of arsenic contamination ever reported. Structure-specific detection of MMAIII, along with arsenite (AsIII), arsenate (AsV), monomethylarsonic acid (MMAV), and dimethylarsinic acid (DMAV), was achieved using liquid chromatography separation with electrospray ionization tandem mass spectromet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 33 publications
0
13
0
Order By: Relevance
“…Considering that As(III) is less toxic than MAs(III), demethylation of MAs(III) to As(III) by Streptomyces might be a detoxification process. It is interesting to note that groundwater from a former herbicide production plant on the Menominee River in Wisconsin was shown to contain high concentrations of MAs(III) (McKnight-Whitford et al ., 2010), which suggests that first microbial reduction of MAs(V) may be widespread and second that MAs(III) is indeed a problem even with an oxidizing atmosphere. Following demethylation, some microorganisms can re-methylate As(III), but, again, the genome of the closely related Streptomyces ceolicolor does not have an arsM gene.…”
Section: Discussionmentioning
confidence: 99%
“…Considering that As(III) is less toxic than MAs(III), demethylation of MAs(III) to As(III) by Streptomyces might be a detoxification process. It is interesting to note that groundwater from a former herbicide production plant on the Menominee River in Wisconsin was shown to contain high concentrations of MAs(III) (McKnight-Whitford et al ., 2010), which suggests that first microbial reduction of MAs(V) may be widespread and second that MAs(III) is indeed a problem even with an oxidizing atmosphere. Following demethylation, some microorganisms can re-methylate As(III), but, again, the genome of the closely related Streptomyces ceolicolor does not have an arsM gene.…”
Section: Discussionmentioning
confidence: 99%
“…Instead of aqueous methyl As, numerous studies showed the formation of gaseous methyl arsines such as Methanobacterium bryantii (McBride 1971), Methanobacterium formicium, Clostridium collagenovorans, Desulfovibrio gigas and Desulfovibrio vulgaris (Michalke et al 2000). Trivalent methyl As (monomethylarsonous acid and dimethylarsinous acid) were proposed to be the intermediates of As methylation according to Challenger's pathway, and have been detected in both environmental samples (Huang et al 2011b;McKnight-Whitford et al 2010) and human cells (Hippler et al 2011). However, both monomethylarsonous acid and dimethylarsinous acid have not yet been found during microbial As methylation.…”
Section: Methylationmentioning
confidence: 99%
“…Arsenic speciation and methylation in freshwater ecosystems has also received attention and this has been driven mostly by studies in As contaminated environments. Methylation processes are similar to that found in the ocean with most of the methylated species being confined to the surface waters and levels in deeper waters depending on a variety of conditions [46][47][48][49][50]. Both seasonally and permanently stratified lakes have been examined and while high levels of the inorganic forms of As are found in anoxic waters, this is not the case for the methylated species.…”
Section: The Distribution Of Methylated Species In the Ocean And In Fmentioning
confidence: 98%